Aerobic fitness and mental well-being: The moderating effect of college student-athlete life stress - Kim, Eunhae (Animo Repository, 2023)
Exercise plays an influential role in improving one’s mental health. Over the years, many researchers have correlated high aerobic fitness to good mental health. However, the correlation remains unclear based on the mixed findings on aerobic capacity (VO2max) and mental well-being found in studies centered on student-athletes. In an attempt to describe this relationship, the researchers examined if college student-athlete life stress may have a moderating effect on the relationship between aerobic fitness and mental well-being in student-athletes. Participants are UAAP season 85 student-athletes from De La Salle University Manila. Data was collected through surveys on mental well-being (SAWS) and stress (CSALSS), and heart rate measurements through a pulse oximeter to estimate VO2max. Results from Pearson’s correlation test indicated a moderate positive correlation between aerobic fitness (VO2max) and mental well-being. Moderation analysis showed that there was a statistically significant moderating effect of college student-athlete life stress on aerobic fitness (VO2max) and mental well-being at low to average levels. No significant correlation can be found in the moderator when the student-athletes’ stress levels are high.